PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI YAYASAN PENDIDIKAN TINGGI RUMPUN LELEMUKU SAUMLAKI - Ignatius Jeujanan; Maartje Paais; Ferdy Leuherry (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to determine the effect of organizational culture, work discipline and organizational commitment on employee performance at the Rumpun Lelemuku Saumlaki Higher Education Foundation either simultaneously or partially. This research method is quantitative with statistical testing using the SPSS v 25 application. The total sample is 55 employees and uses a saturated sample. The results of hypothesis testing show that organizational culture has a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. And simultaneously organizational culture, work discipline and organizational commitment have a significant effect on employee performance. The R value of 2 in this study is 0.564 which means that the variables of organizational culture, work discipline and organizational commitment jointly affect employee performance by 56.4%, while the remaining 43.6% is influenced by variables outside the regression equation or variables that are not examined.